1996
DOI: 10.1038/384463a0
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of self-motion by optic flow processing in single visual interneurons

Abstract: Humans, animals and some mobile robots use visual motion cues for object detection and navigation in structured surroundings. Motion is commonly sensed by large arrays of small field movement detectors, each preferring motion in a particular direction. Self-motion generates distinct 'optic flow fields' in the eyes that depend on the type and direction of the momentary locomotion (rotation, translation). To investigate how the optic flow is processed at the neuronal level, we recorded intracellularly from ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
315
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 371 publications
(326 citation statements)
references
References 20 publications
10
315
1
Order By: Relevance
“…Monocular cells have been found also in the lobula plate of Macroglossum (Wicklein 1994). Although neurons which receive information from both eyes and are sensitive to TPM or RPM can be found in the optic lobes of various species (e.g.¯y: Krapp and Hengstenberg 1996;reviews: Hausen 1981;Hausen and Egelhaaf 1989;bee: DeVoe et al 1982; hawk moth: Collett and Blest 1966) they predominate at subsequent processing levels. Most descending neurons that have been described so far respond best to simulated rotations of the animal.…”
Section: Discussionmentioning
confidence: 99%
“…Monocular cells have been found also in the lobula plate of Macroglossum (Wicklein 1994). Although neurons which receive information from both eyes and are sensitive to TPM or RPM can be found in the optic lobes of various species (e.g.¯y: Krapp and Hengstenberg 1996;reviews: Hausen 1981;Hausen and Egelhaaf 1989;bee: DeVoe et al 1982; hawk moth: Collett and Blest 1966) they predominate at subsequent processing levels. Most descending neurons that have been described so far respond best to simulated rotations of the animal.…”
Section: Discussionmentioning
confidence: 99%
“…To safely fly in cluttered environments, insects instead rely on image motion, also known as optic flow 38,39 , generated by their own displacement relative to the surroundings 40 . It has been experimentally shown that their neural system reacts to optic flow patterns 41,42 to produce a large variety of flight capabilities, such as obstacle avoidance 40,43 , speed maintenance 44 , odometry estimation 45 , wall following and corridor centring 46 , altitude regulation 47,48 , orientation control 49 and landing 50,51 . Optic flow intensity is proportional to the distance from objects only during translational movements, but not during rotational movements when it is proportional to the rotational velocity of the agent.…”
Section: Review Insightmentioning
confidence: 99%
“…In the third visual neuropil (lobula plate) of the fly, several so-called tangential neurons were found to have receptive-field properties adapted to sense particular self-motions (Krapp & Hengstenberg, 1996). They integrate on their extended dendrites the signals of many direction-selective small-field elements.…”
Section: Introductionmentioning
confidence: 99%